(untitled) (Ingenio Magno, 2018)
This article present the results obtained in the denominated project of investigation: Simulations of classic mechanics with the implementation of free software, like tool for the learning of mechanical physics in the students of electronic engineering and systems of the University of the Llanos. A method for the external communication of Python and Blender is explained Engine Game by means of Socket, that corresponds to a method for the interchange of data low between two programs, so that an object in Blender can be controlled Engine Game with an external code of Python, granting like result the simulation in 3D of some phenomena of classic physics. This it is a result of investigation of the group of Dynamic Systems of the University of the Llanos.